Natural gas transits and market power: The case of Turkey - Simon Schulte; Florian Weiser (Institute of Energy Economics at the University of Cologne (EWI), 2017)
Turkey is a key country in order to realize the Southern Gas Corridor (SGC) due to its geographical location. However, as the main transit country within the SGC, Turkey could potentially exert market power with gas transits. Whether Turkey exerts market power or not, is crucial for an economic assessment of the SGC. Hence,the article investigates this issue quantitatively using a global partial equilibrium gas market model. An oligopolistic and a competitive supply structure in Europe in 2030 are considered in the model. If the European gas market in 2030 is characterized by an oligopolistic supply, Turkey is able to exert market power resulting in higher prices compared to competitive transits, in particular in South Eastern Europe. In a competitive market structure, however, the importance of the SGC and thus the potential of Turkish transit market power is limited.
Keywords: L13; L95; 330; Natural Gas; Southern Gas Corridor; Transit Market Power; Mixed Complementarity Problem